Pengaruh Artificial Intelligence terhadap Pembuatan Kontrak Dagang dan Implikasi Hukumnya di Indonesia - Aulia Nur Fauziah; Hudi Yusuf (Penerbit Yayasan Daarul Huda Kruengmane, 2026)
The development of artificial intelligence (AI) has brought about significant changes in commercial contract drafting practices, particularly regarding efficiency, speed, and precision in clause formulation. AI enables business entities to draft, review, and analyze contracts more effectively. However, the application of AI in contract drafting also raises a number of legal issues, especially concerning the validity of agreements, legal liability for system errors, and the protection of parties involved in business relationships. This study aims to analyze the impact of AI on commercial contract drafting and its legal implications in Indonesia. A normative legal research method is employed, utilizing both statutory and conceptual approaches. The research findings indicate that while AI serves as a tool to assist the contract drafting process, the technology cannot replace the intent of the parties, which forms the basis of an agreement's validity. Contract validity must still meet the requirements for a valid agreement as stipulated in the Indonesian Civil Code (KUHPerdata). Furthermore, the use of AI necessitates more adaptive legal regulations to ensure legal certainty and protection for the parties involved. Therefore, the utilization of AI in commercial contracts requires caution and a clear legal framework to prevent future disputes.